2018
DOI: 10.1159/000491616
|View full text |Cite
|
Sign up to set email alerts
|

5’-AMP-Activated Protein Kinase Regulates Goat Sperm Functions via Energy Metabolism In Vitro

Abstract: Background/Aims: ATP is essential for mammalian sperm to survive and maintain fertilizing capacity. AMP-activated protein kinase (AMPK) is a sensor of cellular energy status. The aims of the present study were to explore the localization of AMPK in goat sperm and to investigate whether and how AMPK regulates sperm functions in vitro. Methods: Sperm were treated with AMPK modulators (AICAR, metformin and Compound C) during incubation. Sperm motility was assessed with a computer-assisted spermatozoa analysis sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 41 publications
9
39
1
Order By: Relevance
“…Related to these findings, supplementation of resveratrol increased AMPK activity and was beneficial for protection against cryopreservation-induced oxidative stress of human spermatozoa by improving DNA integrity and transcripts, which were used as markers of sperm quality [ 130 ]. Similar results were obtained in boar [ 131 ] and goat [ 132 ] spermatozoa. In both studies, the addition of resveratrol activated AMPK phosphorylation, allowing the reduction of ROS production, while enhancing the sperm antioxidative defense system such as GSH level and activities of glutathione peroxidase (GPx), SOD, and catalase ( Figure 3 ).…”
Section: Resveratrol Effects On Malessupporting
confidence: 87%
“…Related to these findings, supplementation of resveratrol increased AMPK activity and was beneficial for protection against cryopreservation-induced oxidative stress of human spermatozoa by improving DNA integrity and transcripts, which were used as markers of sperm quality [ 130 ]. Similar results were obtained in boar [ 131 ] and goat [ 132 ] spermatozoa. In both studies, the addition of resveratrol activated AMPK phosphorylation, allowing the reduction of ROS production, while enhancing the sperm antioxidative defense system such as GSH level and activities of glutathione peroxidase (GPx), SOD, and catalase ( Figure 3 ).…”
Section: Resveratrol Effects On Malessupporting
confidence: 87%
“…Bioenergetic functions of sperm mitochondria modulate ATP formation through the mitochondrial ETC, leading to ATP synthesis through the OXPHOS pathway, critical to sustaining sperm viability and motility (23). In human (24) and animal (25,26) sperm, freezing causes damage, decreasing both motility and fertilizing potential. However, some protective effects of melatonin were reported at mitochondrial level (27).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have shown that metformin improves sperm concentration and motility of diabetic rodents, but reduces that of alloxan‐induced diabetic rabbits and healthy animals with normal blood glucose levels . In vitro studies using ejaculated spermatozoa from animal models have shown that metformin improved sperm motility, viability, and the acrosome reaction in chicken and goat models, but inhibited sperm motility in boar and mouse models. So far few studies have investigated the effects of metformin on male reproduction in humans.…”
Section: Introductionmentioning
confidence: 99%